Model of the Cultural Da’wah of the Sunan Gunung Jati and its Relevance with the Current Da’wah of Islam - Hanif Cahyo Adi Kistoro (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2021)
The purpose of research is to analyze the cultural propagation model employed by Sunan Gunung Jati in disseminating Islamic teachings. This study is classified as library research, utilizing primary and secondary sources such as books, journals, and other relevant literature. Data analysis was conducted using content analysis techniques, including source criticism, interpretation, and historiography. The findings reveal that Sunan Gunung Jati’s cultural propagation model relied on petitah-petitih advice and sayings, authority, ipat-ipit guidance and practical wisdom, and magersari community engagement practices. These strategies effectively aligned Islamic teachings with the cultural context of local communities, making them more accessible and acceptable. The use of petitah-petitih and ipat-ipit facilitated the understanding of Islamic principles through culturally familiar forms, while magersari exemplified the application of Islamic values in social interactions (muamalah). This research contributes to the study of Islamic propagation by providing a historical and methodological framework for understanding how cultural integration can enhance the effectiveness of religious teachings. It highlights the adaptability of Islamic propagation strategies to local contexts, fostering a deeper understanding of Islamic values within diverse cultural settings.